Explicit state duration HMM for abnormality detection in sequences of human activity - Luhr, Sebastian; Venkatesh, Svetha; West, Geoffrey; Bui, Hung H. (Springer-Verlag, 2004)
Much of the current work in human behaviour modelling concentrates on activity recognition, recognising actions and events through pose, movement, and gesture analysis. Our work focuses on learning and detecting abnormality in higher level behavioural patterns. The hidden Markov model (HMM) is one approach for learning such behaviours given a vision tracker recording observations about a persons activity. Duration of human activity is an important consideration if we are to accurately model a persons behavioural patterns. We show how the implicit state duration in the HMM can create a situation in which highly abnormal deviation as either less than or more than the usually observed activity duration can fail to be detected and how the explicit state duration HMM (ESD-HMM) helps alleviate the problem.